ENGLISH INSTRUCTORS’ STRATEGIES TO CREATE INTERACTIVE CLASSROOM MANAGEMENT - Andi Yunisma Wardani; Maemuna Muhayyang; Muhalim Muhalim (State University of Makassar, 2026)
The aim of this study is to investigate the methods used by English teachers to establish interactive classroom management and to show how these methods improve student participation at My Liberty English Course in Makassar. The study focused on (1) identifying the strategies used by instructors to establish interactive classroom management and (2) analyzing how those strategies are implemented to sustain student engagement and effectively manage the classroom in interactive English teaching. This research employed a descriptive qualitative case study design involving three instructors teaching at different levels at My Liberty English Course. This research employed a descriptive qualitative case study design involving three instructors teaching at different levels at My Liberty English Course. Semi-structured interviews and observations of classrooms were used to collect the data. Thematic analysis techniques, such as data familiarization, coding, classifying instructional tactics, finding patterns of interaction in the classroom, and making inferences based on recurrent themes, were used to analyze the data. The findings revealed that (1) instructors applied various strategies such as collaborative learning, questioning techniques, structured discussions, role-play, gamified activities, scaffolding, and technology integration to build interactive learning environments; and (2) these strategies were implemented through structured activity planning, clear instructional guidance, gradual support, and flexible classroom facilitation, which helped sustain active participation, maintain classroom order, and promote consistent student engagement. Overall, the study highlights the importance of strategic implementation in balancing interactivity and classroom stability in informal English teaching contexts.Keywords: interactive classroom management, instructors’ strategies, student engagement, English course